Activation of homeless people through Petanque Game - Marta Sarnowska; Sonia Gach; Aleksandra Tereba; Mariusz Czarnecki (Kazimierz Wielki University, 2018)
This study contains a description of homelessness in Poland and a description of a social project aimed at improving the quality of life of homeless people staying in the shelter for homeless men, on ul. Bogedain 5 in Wrocław belonging to the Saint Albert Association, through the activation of homeless people during physical activities with the help of the organized Petanque Games tournament. The homeless team had the opportunity to compete with outsiders, which allowed for social integration and counteracting the exclusion of homeless people. The implementation of tasks was aimed at improving the quality of men's lives as well as popularizing the tradition of playing at Petanque in a group of homeless men, meeting the needs of active activation, integration and social inclusion in this group of people.